REAL-TIME CONTROL SYSTEM FOR URBAN SCHEDULED BUS OPERATION REGULARITY AND ITS MATHEMATICAL FOUNDATIONS (Web of Teachers: Inderscience Research, 2025)
Ensuring the regularity of urban scheduled bus operations is one of the key factors in improving the quality of public transport services. Currently, increasing traffic congestion, delays at bus stops, and the influence of external factors frequently cause deviations from the bus timetable. These issues lead to longer passenger waiting times, bus bunching at stops, and a decrease in overall service reliability. This study proposes improved mathematical modeling and real-time control approaches to maintain the regularity of scheduled bus operations. The research focuses on analyzing bus schedule deviations, dwell times at bus stops, passenger flow dynamics, and traffic conditions. A mathematical model based on average headways and the coefficient of variation is developed to evaluate service regularity. In addition, an optimization algorithm is designed to adjust bus schedules in real-time using continuous monitoring data. The proposed model and control algorithm aim to minimize deviations from the planned timetable by dynamically adapting bus intervals to current conditions. The effectiveness of the model and algorithm was tested using practical data, showing that bus service regularity can be improved by 20-25%. Based on the research results, practical recommendations were developed to enhance the efficiency of urban passenger transportation systems and improve passenger satisfaction.